The Financial Conditions Diversification In Koszalin District Communities In The Years 2010-2014 (Research Bulletins of the Faculty of Economic Sciences, 2017)
The aim of the article is to assess the financial conditions diversification in Koszalin district communities in the years 2010-2014. Figures come from studies of the Ministry of Finance. Financial conditions was determined by non-visual synthetic indicator based on the average value (years 2010-2014) of selected indicators of budget and commitments. It was confirmed that the financial condition of communities depends on the specifics of a given community (functions).
Keywords: community; indicators of budget and commitments; financial condition